Pengembangan Branding dan Pelatihan Pemanfaatan Teknologi Informasi pada Usaha Jus Buah - Ricky Aurelius Nurtanto Diaz; Putu Devi Novayanti; I Made Suandana Astika Pande; Komang Wirayudha Wizu Diaz; Ayu Ratih Cantika Dewi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
The COVID-19 pandemic has caused many changes in people's daily lives. Various ways have been carried out in dealing with this pandemic, like use masks, diligently washing hands and, eating balanced nutrition. The pandemic condition has also raised many new entrepreneurs in various fields. Noona Juice, which is engaged in pure fruit juice, is a form of business that arises due to economic demands and opportunities for increasing public demand for nutritious food and drinks. The condition that occurs to the business of internal community service partners is the lack of an existing market because the marketing process is only carried out through relatives or family contacts and is produced according to the number of orders. Seeing the opportunities that exist for partners, from these conditions the purpose of this community service activity is to help partners in developing their business brands and also assist partners in utilizing financial technology. To achieve this goal, the service team will provide training and workshops in developing partner business branding, online marketing training, and training on the use of financial technology. From the evaluation of the activities that have been carried out, partners are satisfied with the activities that have been carried out.